Penguatan keterampilan berpikir kreatif melalui discovery learning dan media tiktok - Aprilinda, Delpi; Amien, Saiful; Muthohirin, Nafik (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
Creative thinking skills are the ability to find new ways, strategies, and ideas in solving problems. The purpose of this study is to find out whether there is an influence of the discovery learning model using TikTok media on students' creative thinking skills in Islamic cultural history material. The method in this research is the class action method (CAR). The subjects in this study were students of class XI SMAMSA. strengthening students' creative thinking skills in the PAI learning process has increased. This can be seen from the percentage of the pre-cycle stage, which was 46%, which increased to 50% in cycle 1, then in cycle 2 creative thinking skills increased by 15%, namely 65%. By looking at the percentages of the pre-cycle, cycle 1, and cycle 2 stages, it can be said that strengthening the creative thinking skills of Class XI IPA SMAMSA Malang students in PAI learning through discovery learning can be said to be successful.